Kuasa Kolase dalam Ekologi Estetika Postmodern - Wahyudi, Nandang Gumelar (PANTUN: Jurnal Ilmiah Seni Budaya, 2016)
Nowadays, in the field of art, talking about (art) collage is more than just a technical ma" er to attach various other elements - beyond the conventions of painting - on a piece of canvas. It is more than the project that Picasso and Braque have been started in the exploration of experimental cubism to havethe new visual images. Collage today is not merely an expression of rebellion as Kurt Schwi"ers, Raul Hausmann or Hannah Hoch did in the spirit of anti-art that developed in Dada. Nowadays, Collage even transcends the iconic composition prowess ad world of Richard Hamilton or Eduardo Paollozi in pop-art. Thus, Collage in the art map inside postmodern era could be some sort of perspective, a way of thinking and looking, spirit, or footing (“blue-print”)/concept, even the idea of itself. Collage is probably a vast stretch of landscape civilization that celebrates itself among history, knowledge, technology, gaming, market, hospital, war, television and popular culture fanfare. Collage today are the images that were lined-piled around us as a reality that is layered, that seemed real and visible in everyday life - and we’re in it as an inevitable part of the composition of the layers inside collage umpteenth great life.Keywords: art, collage, popular culture, postmodern